Protective Effects of PACAP in Peripheral Organs - Toth, Denes; Szabo, Edina; Tamas, Andrea; Juhasz, Tamas; Horvath, Gabriella; Fabian, Eszter; Opper, Balazs; Szabo, Dora; Maugeri, Grazia; D'Amico, Agata G.; D'Agata, Velia; Vicena, Viktoria; et al. (Frontiers in Endocrinology, 2020)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide widely distributed in the nervous system, where it exerts strong neuroprotective effects. PACAP is also expressed in peripheral organs but its peripheral protective effects have not been summarized so far. Therefore, the aim of the present paper is to review the existing literature regarding the cytoprotective effects of PACAP in non-neuronal cell types, peripheral tissues, and organs. Among others, PACAP has widespread expression in the digestive system, where it shows protective effects in various intestinal pathologies, such as duodenal ulcer, small bowel ischemia, and intestinal inflammation. PACAP is present in both the exocrine and endocrine pancreas as well as liver where it reduces inflammation and steatosis by interfering with hepatic pathology related to obesity. It is found in several exocrine glands and also in urinary organs, where, with its protective effects being mainly published regarding renal pathologies, PACAP is protective in numerous conditions. PACAP displays anti-inflammatory effects in upper and lower airways of the respiratory system. In the skin, it is involved in the development of inflammatory pathology such as psoriasis and also has anti-allergic effects in a model of contact dermatitis. In the non-neuronal part of the visual system, PACAP showed protective effects in pathological conditions of the cornea and retinal pigment epithelial cells. The positive role of PACAP has been demonstrated on the formation and healing processes of cartilage and bone where it also prevents osteoarthritis and rheumatoid arthritis development. The protective role of PACAP was also demonstrated in the cardiovascular system in different pathological processes including hyperglycaemia-induced endothelial dysfunction and age-related vascular changes. In the heart, PACAP protects against ischemia, oxidative stress, and cardiomyopathies. PACAP is also involved in the protection against the development of pre-senile systemic amyloidosis, which is presented in various peripheral organs in PACAP-deficient mice. The studies summarized here provide strong evidence for the cytoprotective effects of the peptide. The survival-promoting effects of PACAP depend on a number of factors which are also shortly discussed in the present review.